Unleashing Academic Excellence through Self-Efficacy among New Global Scholars: Melepaskan Keunggulan Akademik melalui Efikasi Diri di antara Cendekiawan Global Baru - Ariska, Hilda Dwi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores how self-efficacy influences academic self-adjustment among new students in the Faculty of Psychology and Education at the University of Muhammadiyah Sidoarjo. Using quantitative correlational research, we analyzed data from 354 students, with a sample size of 181 determined through the Krejcie-Morgan table. The self-efficacy and academic self-adjustment scales showed high reliability (Cronbach's alpha scores of 0.830 and 0.825, respectively). Results from simple linear regression indicated a positive relationship between self-efficacy and academic self-adjustment, with self-efficacy contributing significantly to 8.2% of the variance. This highlights the importance of bolstering self-efficacy beliefs to aid new students in their academic adaptation during the college transition, particularly in psychology and education faculties. Hilghlight: 1. Self-efficacy influences new college students' academic adaptation.2. Positive correlation between self-efficacy and academic self-adjustment.3. Enhancing self-efficacy beliefs aids academic success in psychology and education. Keywords: Self-efficacy, Academic self-adjustment, New college students, Psychology and Education, Quantitative correlational research